Lobectomy Can Improve the Survival of Patients With Non-small Cell Lung Cancer With Lung Oligometastatic - Wang, Lingwei; Jiao, Fanglei; Dong, Lin; Li, Qinchuan; Liu, Gang; Hu, Xuefei (Frontiers in Surgery, 2021)
Abstract Background: This study was to evaluate the value of lobectomy in the prognosis of Non-small cell lung cancer (NSCLC) patients with primary metastasis based on the Surveillance Epidemiology and End Results (SEER) database. Methods: This was a population-based retrospective study and the clinical data were collected from the National Cancer Institute’s SEER database between 2010 and 2015. The effects of pulmonary surgery and surgical procedures on lung cancer-specific survival (LCSS) and overall survival (OS) were assessed, and the COX regression models were employed to evaluate the survival of primary surgery in patients with primary metastatic NSCLC (pmNSCLC) and the survival of surgical procedure in pmNSCLC patients. Results: A total of 55717 patients diagnosed with pmNSCLC between 2010 and 2015 were enrolled, and pulmonary surgery was indicated in 1575 (2.83%) patients. Surgery was an independent risk factor for LCSS (P<0.001, HR 0.658, 95%CI: 0.637-0.680) and OS (OS: P<0.001, HR 0.665, 95%CI: 0.644-0.686) of pmNSCLC patients. The surgery was associated with better OS (P<0.001, HR 0.678, 95%CI: 0.657-0.699). The site of metastasis was also related to the survival after primary tumor surgery (P=0.001). As compared to the sublobectomy and pneumonectomy, lobectomy improved the LCSS for NSCLC patients with single-organ metastasis, rather than multiple metastases (P<0.001). In patients receiving sublobectomy, lobectomy, and pneumonectomy, the median LCSS was 12 months, 28 months, and 13 months, respectively, and the 5-year LCSS rate was 14.39%, 32.06%, and 17.24%, respectively. Conclusion: The effect of locoregional surgery on the survival of pmNSCLC patients with single-organ metastasis has been underestimated, and lobectomy may be a preferred treatment for patients with single-lung metastasis.